1986
DOI: 10.1139/v86-386
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of carbonyl compounds promoted by silicon hydrides under the influence of trimethylsilyl-based reagents

Abstract: The synthetic utility of hydrosilanes under the influence of trimethylsilyl-based reagents as new reducing systems is described. 1,1,3,3-Tetramethyldisiloxane (TMDS) reagent in combination with iodotrimethylsilane or bromotrimethylsilane produces alkyl halides from aldehydes in good to excellent yields. Polymethylhydrosiloxane (PMS) in the presence of iodotrimethylsilane also produces benzyl iodides in excellent yields. On the contrary, PMS reagent was found unsuitable for the synthesis of benzyl bromides. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…The purities of the products were checked by elemental analysis and comparison of physical properties with those reported in the literature [5].…”
Section: Reagentsmentioning
confidence: 99%
“…The purities of the products were checked by elemental analysis and comparison of physical properties with those reported in the literature [5].…”
Section: Reagentsmentioning
confidence: 99%
“…[35] 1,2-Diphenylethanol (4ff, 5.23 g, 88%) [36] was obtained from deoxybenzoin (2ff) in a similar way. [37] 1-(Iodomethyl)-2-nitrobenzene (59), [38] 1-(iodomethyl)-3-nitrobenzene (60), [39] and 1-(iodomethyl)-4-nitrobenzene (61) [40] were prepared in 88% (5.79 g), 77% (5.06 g), and 78% (5.13 g) isolated yields, respectively, by simply mixing of solutions of the corresponding chlorides in acetone (18.0 mmol in 4.0 mL) and NaI in the same solvent (18.0 mmol in 15.0 mL), by a described procedure. [41] The following alkyl and arylalkyl nitrites were prepared by a known general method: [20] hexyl nitrite (11,3.93 g, 60%), [42] phenylmethyl nitrite (16,4.93 g, 72%).…”
Section: Synthesis Of Intermediates and Substratesmentioning
confidence: 99%
“…Unfortunately this solventless transformation does not work well with ketones or aliphatic aldehydes. 31 Fu and co-workers have shown that PMHS is instrumental in performing Barton-McCombie deoxygenations of thionocarbonates with only catalytic amounts of (Bu 3 Sn) 2 O (eq 17). 5 4 can be applied to reductive aminations (eq 21).…”
Section: O Mementioning
confidence: 99%